Culture in M&A strategy and success: Influence on strategy and implementation - Pennanen, Henrikki (My University, 2024)
Mergers and acquisitions (M&A) are widely used by companies to enable growth together with organic ways, as well as separately. Past studies yet lack a practical understanding of M&A strategy creation as a process, culture’s influence on M&A success, cultural due diligence and how culture relates to M&A strategy and decision making. Purpose of this study is to find connection between M&A strategy and culture. In order to achieve this, Hofstede’s cultural dimension theories are used to define and quantify culture as well as to explain cultural influences behind strategic decisions. In the findings a connection between M&A strategy and culture through cultural dimensions could be formed with a help of some assumptions. Therefore, this thesis proposes that cultural differences of companies could be indicated through cultural dimensions.

Yrityskaupat ovat laajasti käytetty tapa mahdollistaa yrityksen kasvua sekä yhdessä orgaanisen kasvun kanssa, että erikseen. Silti, aikaisemmasta tutkimuksesta on jäänyt tutkimusaukkoja, jotka liittyvät yrityskauppastrategian luontiprosessiin, kulttuurin vaikutukseen yrityskauppojen onnistumisessa, kulttuuriin liittyviin due diligence -käytäntöihin sekä laajempaan ymmärrykseen kulttuurin vaikutuksista yrityskauppastrategioihin ja -päätöksentekoon. Tämän tutkimuksen tarkoituksena on löytää yhtymäkohtia yrityskauppastrategian ja kulttuurin väliltä. Yhtymäkohtien löytämiseksi tutkimuksessa hyödynnetään Geert Hofsteden kehittämää kulttuuristen ulottuvuuksien teoriaa (cultural dimensions theory) määrittämään ja kvantifioimaan kulttuuria terminä sekä selittämään kulttuurin vaikutuksia strategisen päätöksenteon taustalla. Tutkimuksessa löydettiin yhteys yrityskauppastrategian ja kulttuurin välille kulttuuristen ulottuvuuksien teorian kautta, jonkin verran oletuksia hyödyntäen. Tämän pro gradu -tutkimuksen tuloksissa ja johtopäätöksissä todetaan, että yritysten välisiä kulttuurisia eroavaisuuksia voitaisiin havainnollistaa kulttuuristen ulottuvuuksien kautta.
Keywords: mergers, acquisitions, M&A, M&A strategy, culture in M&A, M&A success, national culture, organizational culture, yrityskaupat, yrityskauppastrategia, yrityskauppojen onnistuminen, kansallinen kulttuuri, organisaatiokulttuuri